Ефективність внутрішньоартеріальної поліхіміотерапії хворих на нерезектабельний місцевопоширений рак шлунка - Шалімов, С.О.; Чорний, В.О.; Югрінов, О.Г.; Коробко, В.Б.; Розумій, Д.О.; Осинський, Д.С.; Супруненко, О.О.; Гуніна, Л.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The results of intra-arterial chemotherapy infusion according to the ''FAP+L (FEP+L)'' regime for the treatment of patients with advanced unresectable local gastric cancer are presented and compared with the data in patients of the control group who received the intravenous infusion. The method is accompanied by an increase of the median survival, improvement of the quality of life, and lower toxicity. The use of intra-arterial chemotherapy allows turning a tumor into the resectable state in one-third of the patients.